2021
DOI: 10.1097/dad.0000000000002043
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Extraspinal Subcutaneous Sacrococcygeal Myxopapillary Ependymoma: Case Report and Minireview

Abstract: A 9-year-old girl presented with a slow-growing and painless mass for 7 months in the soft tissue of the sacrococcygeal region. Magnetic resonance imaging revealed a well-circumscribed solid mass located in the subcutaneous soft tissue of the sacrococcygeal area, but not affecting bone structures. The mass was completely removed, and the disorder was diagnosed as myxopapillary ependymoma. In addition, the MYCN gene amplification status of the tumor was evaluated. Extra-axial ependymomas are very rare tumors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Other reportedly negative markers are CD34, CD31, podoplanin, Μelan A, HMB45, SOX10, calretinin, ER, PR, CD30, AFP, SALL4, OCT3/4, synaptophysin, chromogranin, smooth muscle actin, desmin, myogenin, brachyury, H3K27M, p63, 3,8,20,25,29 and in the present study BRAF V600E and neurofilament protein. INI1 expression has been reported as retained in tumor cells 25,29 . Ki‐67 proliferation index is usually in the range of 2%–20%, 21,25,29,32 with higher values in tumors exhibiting anaplastic features, 20 and generally a greater propensity to metastasize 21 …”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Other reportedly negative markers are CD34, CD31, podoplanin, Μelan A, HMB45, SOX10, calretinin, ER, PR, CD30, AFP, SALL4, OCT3/4, synaptophysin, chromogranin, smooth muscle actin, desmin, myogenin, brachyury, H3K27M, p63, 3,8,20,25,29 and in the present study BRAF V600E and neurofilament protein. INI1 expression has been reported as retained in tumor cells 25,29 . Ki‐67 proliferation index is usually in the range of 2%–20%, 21,25,29,32 with higher values in tumors exhibiting anaplastic features, 20 and generally a greater propensity to metastasize 21 …”
Section: Discussionsupporting
confidence: 60%
“…Chromosomal copy number changes are frequent, including chromosome 7 polysomy, 35 gains of chromosomes 9, 16, and 18, and losses of chromosomes 22q, 10, and 13q 35 . Studies by fluorescent in situ hybridization have not shown amplification of EGFR 36 or MYCN genes 29 . MPEs' gene expression profile includes upregulation of HOXB13 , NEFL , and PDGFRA , also detectable at the protein level by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations